2018
DOI: 10.3727/096504017x15031557924123
|View full text |Cite
|
Sign up to set email alerts
|

-1,3-Galactosyl-O-Glycosyl-Glycoprotein -1,6-N-Acetylglucosaminyltransferase 3 Increases MCAM Stability, Which Enhances S100A8/A9-Mediated Cancer Motility

Abstract: We previously identified novel S100A8/A9 receptors, extracellular matrix metalloproteinase inducer (EMMPRIN), melanoma cell adhesion molecule (MCAM), activated leukocyte cell adhesion molecule (ALCAM), and neuroplastin (NPTN) β, that are critically involved in S100A8/A9-mediated cancer metastasis and inflammation when expressed at high levels. However, little is known about the presence of any cancer-specific mechanism(s) that modifies these receptors, further inducing upregulation at protein levels without an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 33 publications
1
31
0
Order By: Relevance
“…We also established several A549 stable clones that showed indefinitely stable expression of the aberrant genes of interest at much higher levels. Based on the pIDT‐SMART (C‐TSC) vector, we made two improved vectors for stable expression with significantly higher level, named pSAKA‐1B and pSAKA‐4B . The expression vector pSAKA‐1B is specifically adapted to Chinese hamster ovary (CHO) cells, while pSAKA‐4B is useful for a wide range of diverse cell lines from different kinds of mammalian species in a constant manner.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also established several A549 stable clones that showed indefinitely stable expression of the aberrant genes of interest at much higher levels. Based on the pIDT‐SMART (C‐TSC) vector, we made two improved vectors for stable expression with significantly higher level, named pSAKA‐1B and pSAKA‐4B . The expression vector pSAKA‐1B is specifically adapted to Chinese hamster ovary (CHO) cells, while pSAKA‐4B is useful for a wide range of diverse cell lines from different kinds of mammalian species in a constant manner.…”
Section: Methodsmentioning
confidence: 99%
“…Besides classical S100A8/A9 receptors, toll-like receptor 4 (TLR4) 4,5 and receptor for advanced glycation end products (RAGE), 5,6 we have reported the presence of the important novel receptors including extracellular matrix metalloproteinase inducer (EMMPRIN), neuroplastin (NPTN)α and β, melanoma cell adhesion molecule (MCAM) and activated leukocyte cell adhesion molecule (ALCAM). [7][8][9][10][11][12] Among these receptors, we found that lung cancer cell lines highly express NPTNβ compared with normal cells lines ( Figure S1A). This finding was supported by the result of immunohistochemistry showing that NPTNβ was highly positive in lung cancer cells and that S100A8/A9 appeared in either cancer cells or the surrounding stroma in clinical specimens, suggesting that extracellular S100A8/A9 physiologically acts on cell surface NPTNβ in cancer cells in an autocrine manner as well as a paracrine manner ( Figure 1).…”
Section: Nptn and S100a8/a9 Are Highly Expressed In Lung Cancermentioning
confidence: 99%
“…Namely, extracellular S100A8/A9 secreted from the lungs attracts melanoma cells from distant skin foci, acting as strong ‘soil signals’ to receptors in the cancer cells that function as ‘S100A8/A9‐soil signal sensors’. These sensors include the renowned Toll‐like receptor 4 (TLR4), receptor for advanced glycation end products (RAGE), and novel receptors that we have identified, MCAM, ALCAM, EMMPRIN and NPTNα and β.…”
Section: Introductionmentioning
confidence: 99%
“…2 We then found further evidence of other important novel soil sensors for S100A8/A9: EMMPRIN, 3 NPTNβ, 4 MCAM and ALCAM. 5,6 We named the proteins "S100 soil sensor receptors, abbreviated as SSSRs." 5,6 The relationship between S100A8/A9 and these receptors may be applicable to broad cancer species since S100A8/A9 is also utilized by breast cancer cells for lung tropic metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 We named the proteins "S100 soil sensor receptors, abbreviated as SSSRs." 5,6 The relationship between S100A8/A9 and these receptors may be applicable to broad cancer species since S100A8/A9 is also utilized by breast cancer cells for lung tropic metastasis. 7 Since these receptors seem to be differently expressed depending on the cancer species and since their expression seems to be upregulated in response to the progression of cancer malignancy (our study and our ongoing studies), the S100A8/A9-SSSRs axis therefore may act as an important mediator in "seed and soil" metastasis in multiple cancer species.…”
Section: Introductionmentioning
confidence: 99%